Knowledge and attitude towards emergency contraception among undergraduate medical students - Gajera, Aditya N.; Barvaliya, Manish J.; Shukla, Apexa; Tripathi, C. B. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Studying the knowledge and attitude of medical students towards emergency contraception, as they are the future medical professionals and they will serve as the main channel for providing proper knowledge and making positive impression of it in general population. The objective of the study was to assess the knowledge and attitude of undergraduate medical students towards emergency contraception. Methods: Medical students were given pre-validated questionnaire and divided in two groups. Group A students did not learn about emergency contraception, whereas group B students learnt about it. Interview of both groups were conducted separately. For group A, 1 hour seminar was conducted and after 7 days, same questionnaire was provided again for data collection. Results: 154 students were included in group A whereas 162 students in group B. Average knowledge and attitude was significantly increased after seminar in group A [knowledge 41±16.88% vs. 59.32±14.46%; P<0.05; attitude 36.24±10.93 vs. 41.5±10.87; P<0.05]. Average knowledge of group B students was 64.73±12.15% whereas average attitude score was 42.9±9.79. Amongst all, 86.4%, 87% and 89.3% students were not able to describe about emergency contraception, different methods and advantages of intra-uterine device as emergency contraception, respectively. There are 82.1% students showed positive interest in learning more about emergency contraception and 70.1% agreed to recommend its use in future. Students having good knowledge showed more positive attitude towards emergency contraception [r= 0.41, P<0.05]. Conclusions: Students have poor knowledge of special issues arises with emergency contraception. Proper attention should be given to these aspects during their teaching. Students have shown their positive interest to learn more about emergency contraception. Objective based seminar will be more helpful in improving knowledge and attitude.